2000
DOI: 10.1093/jn/130.4.792
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Diacylglycerol Suppresses Accumulation of Body Fat Compared to Triacylglycerol in Men in a Double-Blind Controlled Trial

Abstract: We examined the effects of the long-term ingestion of dietary diacylglycerols (DG) in a double-blind controlled study of human lipid metabolism. Healthy men (n = 38; aged from 27 to 49 y, body mass index (BMI) ranging from 21.8 to 27.4 kg/m(2)) completed the study. To accustom the subjects to the test diets prior to the experiment, they were supplied with test diets of triacylglycerol (TG) oil for 4 wk (control period). The test oils (10 g/d) were included in bread, mayonnaise or shortbread and served for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
165
1
5

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(183 citation statements)
references
References 22 publications
12
165
1
5
Order By: Relevance
“…12,13 In this study, the cumulative recovery rate of 13 CO 2 was assessed as an indicator of dietary fat oxidation. The 13 Clabelled triolein was used to determine if DAG consumption alters the oxidation of TAG derived from the test meal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 In this study, the cumulative recovery rate of 13 CO 2 was assessed as an indicator of dietary fat oxidation. The 13 Clabelled triolein was used to determine if DAG consumption alters the oxidation of TAG derived from the test meal.…”
Section: Discussionmentioning
confidence: 99%
“…11 Human studies in the US and Japan have demonstrated that long-term consumption of a diet containing DAG oil enhances loss of body weight and BF compared with a TAG oil with a similar fatty acid composition. 12,13 Animal studies have shown that both b-oxidation and expression of lipid metabolism-related genes in the liver and small intestine are enhanced with chronic DAG oil ingestion compared with TAG oil ingestion. [14][15][16] Several human studies have shown greater fat oxidation and/or lower respiratory quotient with short-term DAG oil consumption (single meal, 17 1 8 and 4 days 18 ) compared with TAG oil consumption.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 2, the fatty acid composition of DG was indistinguishable from that of TG. The majority of fatty acids in TG were present as TG, while the majority of fatty acids in DG were recovered mainly as 1,3-and to a lesser extent as 1,2-diacylglycerol (the 1,3-a1,2-ratio was 7X3; Nagao et al, 2000). Packets containing 10 g portions of DG or TG mixed with the daily PS dose of 500 mg were prepared as PSaDG or PSaTG mayonnaise (test mayonnaise).…”
Section: Subjects and Experimental Designmentioning
confidence: 99%
“…Although the physiological functions of individual components could not be statistically detected by modulating the lipid profiles of rats, it seems that the physiological impact might be enhanced by a combination of components that lower serum TG concentrations. 5,25) In the case of the cholesterol diets, however, the physiological function of SPI was thought to be characteristic. That is, not only serum and liver cholesterol but also the TG concentrations of the rats fed the SPI diets were improved.…”
Section: Discussionmentioning
confidence: 99%